Spiropyran-functionalized polymer-carbon nanotube hybrids for dynamic optical memory devices and UV sensors - Leinen, Merve; Klein, Patrick; Sebastian, Finn; Zorn, Nicolas; Adamczyk, Sylwia; Allard, Sybille; Scherf, Ullrich; Zaumseil, Jana (Advanced electronic materials, 2020)
Nanohybrids of purified semiconducting single-walled carbon nanotubes and conjugated polymers with attached spiropyran moieties are created as photoresponsive materials for optical memory devices and ultraviolet (UV) light sensors. The hybrids respond to UV light exposure in air with photoisomerization of the spiropyran groups to merocyanine, resulting in significant and persistent p-doping of the nanotubes, as confirmed by photoluminescence quenching and trion emission. The increased carrier concentration after illumination and the inherently high mobility of carbon nanotubes enable an up to two orders of magnitude increased conductivity of the nanotube/polymer hybrid networks in simple two-terminal devices operated at very low bias. The photodoping decays very slowly in the dark and increases further with every illumination dose. However, it can be completely reversed by heating for a few seconds. Thin film devices based on these photoresponsive polymer/nanotube hybrids show great potential as simple and resettable UV dosimeters and optical memory elements.
First published: 16 September 2020
Gesehen am 26.10.2021